A New Low‐Bandgap Polymer Containing Benzene‐Fused Quinoxaline: Significantly Enhanced Performance Caused by One Additional Benzene Ring. Issue 3 (11th December 2012) - Li, Shuang; Li, Aiyuan; Yu, Jian; Zhong, Aoshu; Chen, Su'an; Tang, Runli; Deng, Xianyu; Qin, Jingui; Li, Qianqian; Li, Zhen
Abstract Two new alkoxy‐substituted quinoxaline (Qx)‐based copolymers, PBDTQx and PBDTPz, are designed and synthesized. The only difference between these two polymers is that two methyl groups of the Qx are replaced by one additional fused benzene ring. The UV–Vis absorptions, thermal stability, energy levels, field‐effect carrier mobility, and photovoltaic characteristics of the two copolymers are systematically evaluated to understand the relationships between the polymer structure at the molecular level and the photovoltaic performances. Photovoltaic cells based on the PBDTPz with a structure of ITO/PEDOT:PSS/Polymer:PC71BM/PEO/Ca/Al exhibit a promising efficiency of 4.40%, while that of PBDTQx is relatively much poorer.